HADIS EKONOMI KEUNTUNGAN TANPA MENANGGUNG RISIKO - Husni Husni (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2017)
Hadith prohibition of taking profits without taking risks is one of the important traditions. This hadith is one of the foundations of the principle of al-kharâj bi al-dhamân. From the various narrations that exist, this hadith is categorized as shaḥîḥ with a continuous sanad and maknawi qualified hadith mutawâtir. From this point of view, the hadith gives the science of dharûrî. From the point of meaning there is no significant disguise on the hadith. However, at least, there are four most important obstacles in the application of the hadith. Keywords: Takhrij, Profit, Risk, Hadith